Prevalence of post-traumatic stress disorders and associated factors one month after the outbreak of the COVID-19 among the public in southwestern China: a cross-sectional study - Lei Lei (BMC, 2021)
Abstract Background The Coronavirus Disease 2019 (COVID-19) pandemic has rapidly spread across the whole world and brought strong psychological impact. This study aimed to evaluate the prevalence of post-traumatic stress disorders (PTSD) in the general people of southwestern China and associated factors 1 month after the outbreak of the COVID-19. Methods This study was started on 4–10 Feb 2020 based on online survey. The present work was carried out in the provinces of southeastern China, including Sichuan Province, Guizhou Province, Yunnan Province, and Chongqing City.1593 respondents aged 18 years and above administered to this study. Data on whether they have experienced confirmed or suspected COVID-19 of themselves/family members/acquaintances were also collected, and based on ‘yes’ answers, the number of affected individuals (via COVID-19) were categorized into four exposure levels i.e., non-affected, less, moderately, or significantly affected. The civilian version of the PTSD checklist and the self-reported information about COVID-19 were used. Results The prevalence of PTSD was approximately 25.2%(n = 401/1593). The chances of developing PTSD were 6.053(OR = 6.053, 95% CI 1.394 to 26.280) or 3.673(OR = 3.673, 95% CI 1.738 to 7.765) times higher among respondents who had been significantly and moderately affected than those who had not been affected, accordingly. Male (OR = 1.484, 95% CI 1.147 to 1.920),younger age individuals (40 ~ 49 age group/<30 age group, OR = 0.395, 95% CI 0.258 to 0.606) and health care workers (OR = 1.788, 95% CI 1.155 to 2.277) were at higher risk of developing PTSD. Conclusion Our findings highlight that a positive correlation between the pandemic and PTSD. It is urgent to establish a screening and prevention systems for the population who are significantly exposed to COVID-19,and provide different psychological intervention strategies for different groups.